AB0230 Anorectal involvement in very early systemic sclerosis (SSC). (23rd January 2014) - Lepri, G.; Bellando Randone, S.; Guiducci, S.; Giani, I.; Carnesecchi, G.; Bruni, C.; Blagojevic, J.; Radicati, A.; Pucciani, F.; Matucci Cerinic, M.
Abstract : Background: In SSc anorectal dysfunction is reported in 50-70% with a high impact on patients' quality of life. Objectives: Evaluation of anorectal involvement and its correlation with esophageal involvement in very early SSc. Methods: 56 patients (55 female), mean age 49, 2±14 years, with very early SSc were evaluated with anorectal and esophageal manometry. The demographic data, anorectal symptoms (fecal incontinence and constipation), Raynaud phenomenon (presence/absence, duration), autoantibodies profile (anticentromere antibodies [ACA], antinuclear antibodies [ANA], anti-Scl70 antibodies [Scl70]), videocapillaroscopy patterns (Normal, Early, Active, Late), puffy fingers, digital ulcers were recorded for all patients. Results: Anorectal manometry was abnormal in 85% of patients, in these patients an esophageal involvement was found (absence of esophageal peristalsis in 29% of patients and abnormal peristalsis in 67, 7% of patients). Anorectal symptoms were found in 5 patients (12, 5%). In 16 patients anorectal manometry was not performed because of scarce tolerance of the procedure. Conclusions: Anorectal disorders are frequently detected in very early SSc even in asymptomatic patients. Our data demostrate that very early SSc is charaterized by contemporary esophageal and anorectal involvement. Disclosure of Interest: None Declared